Timeliness of vaccination in infants followed by primary-care pediatricians in France - Anne-Charlotte Bailly; Pauline Gras; Jean-François Lienhardt; Jean-Christophe Requillart; François Vié-; Alain Martinot; François Dubos (Taylor & Francis Group, 2018)
Vaccination status is more often evaluated by up-to-date vaccination coverage rather than timeliness of immunization. Delaying vaccination may be dangerous during infancy. The aim of this study was to identify the importance of potentially dangerous vaccination delay (previously defined) and determinants of these delays. We conducted a national, prospective, vaccination survey in June 2014, with primary care pediatricians. Children, 2 to 24 months of age, were included. Data about vaccination were extracted from their health books. Additional data were collected through a standardized questionnaire. Vaccine coverage rate and timeliness were calculated. Variables associated with a potentially dangerous vaccination delay as previously defined were determined by a multivariable analysis. Among the 443 included children (mean age 10.8 months, 49% males), 13% to 58% of vaccine doses according to vaccine type were done with a potentially dangerous delay. Globally, 47% of children had at least one potentially dangerous immunization delay. We identified two risk factors of potentially dangerous delayed immunization globally: an increasing age of the child (adjusted odds ratio: 1.2, 95% confidence interval [CI]: 1.1-1.3, p < 10−3), and a working mother (adjusted OR: 2.4, 95% CI: 1.2-4.7, p = 0.01). Despite a good vaccine coverage rate, a large number of children had a potentially dangerous vaccination delay. A high level of vigilance regarding these immunization delays, and particularly to the patients sharing the risk factors of immunization delay identified here, can increase quality and effectiveness of the vaccine protection.